What Counts as 4-H in My Programs - Marilyn N. Norman; Joy C. Jordan (EDIS)
This document is 4HS FS101.12, one of a series of the Florida 4-H Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida.